The Challenges of Digital Banking in Today’s Banking Industry - Haryono, Didi; Saha Ghafur, A. Hanief; Rusliwa Somantri, Gumilar (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Nowadays, the development of technology is very rapid. Technology is used in almost every area of life. The same applies to the banking industry. The digital era has changed the pattern of the banking business. The ease of use of this technology is expected to bring convenience and speed to transactions called digital banking. Digital banking is a banking service that creates a digital economy that is pursued by many new products issued by banks through technology that utilizes digital technology to meet customer needs and facilitate transactions with customers. The research method is with a Qualitative Descriptive approach and the data used in the survey is using literature, documents, news magazines, interviews, and direct observation of what is happening in the rapidly growing financial technology, taking into account the laws and regulations. Namely Bank Indonesia and the Financial Services Authority. The banking industry is facing increasing challenges in the digital world and progress in the coming years is unstoppable. This is because banks not only have to compete with other banks but also with other financial technology companies that provide security and convenience to their users in the digital economy era. The public needs to be educated about digital banking services. As a tech-savvy society, there is no need to hesitate to make technological advances, but also need to be careful not to sacrifice technological advances. The public needs to be educated about digital banking services.